2021
DOI: 10.1007/s00586-021-06759-7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of global sagittal malalignment to fatty infiltration in the aging spine

Abstract: Purpose To investigate associations between muscle size, fat infiltration (FI), and global sagittal alignment in patients with adult spinal deformity (ASD). Methods Retrospective cohort study was conducted on a single-institution database of ASD patients with preoperative radiographs and CTs. Following multiplanar reconstructions of CTs, images in the plane of each vertebra were generated. The posterior vertebral musculature (PVM) was contoured on axial im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…Why was pelvis flexion ROM also involved in the present regression model? Again, only LuM MFI (not fibrosis) would explain the positive relationship with ECHO LuM , as an increased MFI in the posterior vertebral muscles (erector spinae + LuM) has been associated with pelvic retroversion (Elysee et al, 2021; Lee et al, 2022; Zhang et al, 2021). However, MFI in LuM was not enough to induce a change in pelvic inclination in 93 healthy controls (Menezes‐Reis et al, 2018), which was later confirmed in a study showing a relationship with the erector spinae MFI but not LuM MFI in participants with spinal deformity (Miura et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Why was pelvis flexion ROM also involved in the present regression model? Again, only LuM MFI (not fibrosis) would explain the positive relationship with ECHO LuM , as an increased MFI in the posterior vertebral muscles (erector spinae + LuM) has been associated with pelvic retroversion (Elysee et al, 2021; Lee et al, 2022; Zhang et al, 2021). However, MFI in LuM was not enough to induce a change in pelvic inclination in 93 healthy controls (Menezes‐Reis et al, 2018), which was later confirmed in a study showing a relationship with the erector spinae MFI but not LuM MFI in participants with spinal deformity (Miura et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Power analysis was based on data of previous studies on the infiltration rate of LDH and scoliosis [ 14 , 15 ] and showed that at least 23 patients were needed in each group to reach a high statistical power (> 0.8). After applying inclusion and exclusion criteria we enrolled 50 patients in our analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Increased vertebral bone marrow fat content can be associated with vertebral fractures and back pain spine in patients with adult spinal deformity (17). And in relation to this, numerous studies have demonstrated a relationship between sagittal spinal imbalance and back pain (18,19).…”
Section: Editorialmentioning
confidence: 99%
“…In this sense, some authors have demonstrated an association between lumbar vertebral BMF content and paraspinal muscle fat composition ( 13 , 14 ), and at the same time a correlation between paraspinal muscle fat infiltration with a higher number of vertebral fractures and a lower BMD ( 14 - 16 ). It is worth highlighting the study published by Elysee et al where the authors found that global sagittal malalignment is related to fat infiltration of the posterior vertebral musculature throughout the lumbar and thoracic spine in patients with adult spinal deformity ( 17 ). And in relation to this, numerous studies have demonstrated a relationship between sagittal spinal imbalance and back pain ( 18 , 19 ).…”
unclassified